Beginning science teachers’ online classes: A narrative inquiry - Jleian Mard M. Loseñara; Catherine P. Loseñara (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
With the unprecedented shift to online or flexible learning modes, both teachers and students adapt to the new normal of education. A qualitative study aimed to draw out the voices of three beginning science teachers, the study utilized the narrative inquiry approach through in-depth interviews. It was found that beginning science teachers are faced with challenges: transitioning to the actual teaching practice and adjusting to the new normal in education. Beginning science teachers voiced out their challenges, including adapting to the culture of the new generation of students, access to a stable internet connection, problems with technology use, and teaching-learning process adjustments. Coping strategies include creative and responsive adjustments to teaching-learning, assessment of learning, learning mode, and internet connection problems and online platforms. Their stories serve as a springboard for interventions that guide and assist beginning teachers.